Faktor yang Mempengaruhi Kesulitan Berhenti Merokok pada Mahasiswa Akper Kesdam I/BB Medan - Ade Irma Khairani; Suvi Novida; Muchti Yuda Pratama (Jurnal Kesmas Asclepius, 2019)
This study aims to determine the factors that influence the difficulty of Akper Kesdam I / BB Medan students to stop smoking. The research design that will be used is descriptive qualitative with a phenomenological study approach. The results showed all informants started smoking while still in school. From 12 informants, found 6 (50%) informants started smoking while sitting in high school, 4 (33%) informants started smoking while sitting in junior high school, and found 2 (17%) informants started smoking while still sitting in elementary school. Conclusion, the difficulty factor for the students of Akper Kesdam I / BB Medan to stop smoking is self (personal), addiction to cigarettes, the influence of the social environment, peers, ease of getting cigarettes and the existence of people who become role models of smoking. Keywords: Stop Smoking, Difficulty Factors